2001
DOI: 10.1108/eum0000000006497
|View full text |Cite
|
Sign up to set email alerts
|

Applying Tittle’s control balance theory to police deviance

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 26 publications
4
62
0
Order By: Relevance
“…These studies revealed that control imbalances of both types were related to assault (Baron & Forde, 2007;Piquero & Hickman, 1999, theft (Baron & Forde, 2007), deviant sexual practices (Piquero & Hickman, 1999), eating disorders , using others school work Higgens & Lauterbach, 2004), cheating (Curry, 2005), and victimization (Piquero & Hickman, 2003). Other work discovered that only control balance surpluses were related to corporate offending (Piquero and Piquero, 2006) and only control balance deficits were related to police deviance (Hickman, Piquero, Lawton, & Greene, 2001). DeLisi and Hochstetler (2002) found a number of sphere specific control balance ratios were better related to aggregates offenses of defiance and predation than exploitation, decadence, or submission.…”
Section: Past Researchmentioning
confidence: 91%
See 2 more Smart Citations
“…These studies revealed that control imbalances of both types were related to assault (Baron & Forde, 2007;Piquero & Hickman, 1999, theft (Baron & Forde, 2007), deviant sexual practices (Piquero & Hickman, 1999), eating disorders , using others school work Higgens & Lauterbach, 2004), cheating (Curry, 2005), and victimization (Piquero & Hickman, 2003). Other work discovered that only control balance surpluses were related to corporate offending (Piquero and Piquero, 2006) and only control balance deficits were related to police deviance (Hickman, Piquero, Lawton, & Greene, 2001). DeLisi and Hochstetler (2002) found a number of sphere specific control balance ratios were better related to aggregates offenses of defiance and predation than exploitation, decadence, or submission.…”
Section: Past Researchmentioning
confidence: 91%
“…The bulk of the limited number of available empirical tests on the control balance perspective have found that both control balance deficits and control balance surpluses were related to a range of deviant behaviors (although see Hickman, Piquero, Lawton, & Greene, 2001;Piquero & Piquero, 2006). These studies revealed that control imbalances of both types were related to assault (Baron & Forde, 2007;Piquero & Hickman, 1999, theft (Baron & Forde, 2007), deviant sexual practices (Piquero & Hickman, 1999), eating disorders , using others school work Higgens & Lauterbach, 2004), cheating (Curry, 2005), and victimization (Piquero & Hickman, 2003).…”
Section: Past Researchmentioning
confidence: 92%
See 1 more Smart Citation
“…Under the latter approach, developed by Tittle (1995), individuals possessing either control deficits (i.e., they were subject to more control than they exercised) or control surpluses (i.e., they enjoyed more control than they were subject to) were likely to commit deviant acts. In testing the applicability of control balance theory to police deviance with a sample of police officers in Philadelphia, Hickman et al (2001) found that officers who were experiencing control deficits were more likely to report fellow officers for misconduct. In general, however, there were relatively few efforts that systematically applied formal criminological models to the study of police misconduct.…”
Section: Explaining Police Misconductmentioning
confidence: 99%
“…Vignettes were provided to police officers who were asked their opinion about the use of unnecessary force and the likelihood that another officer would report that force to a supervisor (the dependent variables). The vignette design has been used to study the decision-making of officers (Eterno 2003) and to examine the opinion of police officers regarding the behavior of other officers (Hickman et al 2001). Several factors were included in each vignette (discussed below).…”
Section: Datamentioning
confidence: 99%